2017
DOI: 10.5547/01956574.38.si1.aarg
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Renewable Energy Policies in E.U.15, U.S. and China: A Bayesian DSGE Model

Abstract: The promotion of renewable energy sources (RES) by governments is one way of helping countries to meet their energy needs while lowering greenhouse gas emissions. In this paper, we examine the role of energy policy in RES promotion, based on a carbon tax and RES price subsidy, at a time of technological and demand shocks in the European Union (E.U.) 15 countries, the United States (U.S.) and China, focusing on the macroeconomic implications. Using a dynamic stochastic general equilibrium model for RES and foss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 56 publications
0
15
0
Order By: Relevance
“… Argentiero et al (2017) ξ 3.50 footprintnetwork.org Ψ 2.00 Smets and Wouters (2003) 2.00 Smets and Wouters (2003) 0.90 Yang et al (2020) 0.06 Yang et al (2020) 1.35 Forastieri et al (2011) 1.00 Forastieri et al (2011) 0.00 Own assumption d 0.50 Ispra (2020) e 0.45 Ispra (2020) ρ 0.96 European Commission (2014) 0.90 e.g. Argentiero et al (2017) 0.90 e.g. Argentiero et al (2017) 0.06 Own elaboration based on ISPRA and Adyel, 2020 0.10 e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“… Argentiero et al (2017) ξ 3.50 footprintnetwork.org Ψ 2.00 Smets and Wouters (2003) 2.00 Smets and Wouters (2003) 0.90 Yang et al (2020) 0.06 Yang et al (2020) 1.35 Forastieri et al (2011) 1.00 Forastieri et al (2011) 0.00 Own assumption d 0.50 Ispra (2020) e 0.45 Ispra (2020) ρ 0.96 European Commission (2014) 0.90 e.g. Argentiero et al (2017) 0.90 e.g. Argentiero et al (2017) 0.06 Own elaboration based on ISPRA and Adyel, 2020 0.10 e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The second strand of literature which is relevant for our methodological strategy is the one addressing environmental policy in explicitly dynamic economic models. Among others, the closest to our work are those by Argentiero et al (2017) , who focus on renewable energy policies, and Annicchiarico and Di Dio (2015) , who develop a (New Keynesian) DSGE framework to analyse the linkages between environmental policy and business cycle fluctuations 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The model was simulated and the findings favour the use of a stock of public capital in place of subsidies because subsidies reflect a short run policy which does not encourage investors' confidence. Argentiero et al (2017) analysed the role of environmental policy in renewable energy sources based on carbon tax and renewable energy subsidies for 15 members of the European Union, United States and China within a DSGE model incorporating both a fossilfuel and renewable energy sector. The model was solved using Bayesian techniques and the results showed that in the presence of a total factor productivity shock in the fossil-fuel sector, an energy policy shock serves as a driving force for dampening the energy sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2 Hassler and Krusell (2012) also introduced TFP shocks into a regional integrated model of climate and the economy (RICE) to provide an integrated investigation of climate policies on oil-producing and oil-importing countries. The environmental DSGE modelling literature has been extended to include other shocks, such as environmental shocks (Angelopoulos, Economides and Philippopoulos 2013), energy price shocks (Roach 2014), consumption shocks (Argentiero et al 2017) and nominal shocks (Annicchiarico and Di Dio 2015). The contribution of the current article to the literature is not introducing a new type of shock, but comparing the economic and environmental effects of two popular emissions reduction regimes of fixed and variable emissions taxes when a shock occurs.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in Heutel (2012) and Angelopoulos, Economides and Philippopoulos (2013), the tax rate changes in every period. Hassler and Krusell (2012) specify climate policies in terms of taxation on oil, Fischer and Springborn (2011) and Annicchiarico and Di Dio (2015) include variable tax, cap and an intensity target, and Tumen et al (2016) and Argentiero et al (2017) consider taxes on fossil fuels and subsidies on renewable energy. A review of implemented tax policies in countries such as Finland, Norway, Switzerland and Japan (World Bank 2016), however, indicates that the tax rates in their programs have been estimated and pre-announced a few periods (even years) in advance, and have been kept constant over several periods.…”
Section: Introductionmentioning
confidence: 99%